Elective neck dissection in oral squamous cell carcinoma: Past, present and future. (March 2019) - de Bree, Remco; Takes, Robert P.; Shah, Jatin P.; Hamoir, Marc; Kowalski, Luiz P.; Robbins, K. Thomas; Rodrigo, Juan P.; Sanabria, Alvaro; Medina, Jesus E.; Rinaldo, Alessandra; Shaha, Ashok R.; Silver, Carl; et al.
Highlights: Results of decision analysis are only as good as the data that are fed into a model. Recommendations for the management of the clinically negative neck are not immutable. Variations in clinical practice may result in different management of the neck. Models and decision support systems must be developed to optimize individual choices. Abstract: In 1994 a decision analysis, based on the literature and utility ratings for outcome by a panel of experienced head and neck physicians, was presented which showed a threshold probability of occult metastases of 20% to recommend elective treatment of the neck. It was stated that recommendations for the management of the cN0 neck are not immutable and should be reconfigured to determine the optimal management based on different sets of underlying assumptions. Although much has changed and is published in the almost 25 years after its publication, up to date this figure is still mentioned in the context of decisions on treatment of the clinically negative (cN0) neck. Therefore, we critically reviewed the developments in diagnostics and therapy and modeling approaches in the context of decisions on treatment of the cN0 neck. However, the results of studies on treatment of the cN0 neck cannot be translated to other settings due to significant differences in relevant variables such as population, culture, diagnostic work-up, follow-up, costs, institutional preferences and other factors. Moreover, patients may have personal preferences and may weigh oncologic outcomes versus morbidity and quality of life differently. Therefore, instead of trying to establish "the" best strategy for the cN0 neck or "the" optimal cut-off point for elective neck treatment, the approach to optimize the management of the cN0 neck would be to develop and implement models and decision support systems that can serve to optimize choices depending on individual, institutional, population and other relevant variables.